Synthesis of Au sponges based on agarose template. (15th April 2021) - Kwak, Soyul; Jang, Seohyeon; Park, Soomin; Kang, Jihyeon; Kim, Tae Yong; Nam, Inho
Abstract: Metal-containing porous structures have been widely used in the fields of electrochemical and acid-base catalysis, bio-filtration, and heat-dissipation. Here, we propose a method for the fabrication of robust macroporous metallic sponges using agarose gel and HAuCl4 as soft-sacrificial templates and Au precursor, respectively. We demonstrate that the preparation of self-supporting macroporous Au sponges is practicable by heating the soft-agarose framework in the range of temperatures from 200 to 500°C. Before the calcination of agarose framework, Au precursor was reduced using NaBH4 . A series of data obtained from X-ray photoelectron spectroscopy and X-ray diffraction indicates that the Au sponges were well synthesized with high crystallinity. The structural properties of porous Au were methodically investigated using Rietveld refinement and density-functional-theory calculations. The use of agarose gel as a soft template for the fabrication of metallic sponges has various advantages over conventional methods, as this approach is environmentally benign, shape-controllable, inexpensive, and scalable for mass production. Graphical abstract: Image, graphical abstract